Dual Peril: A rare case of simultaneous Bartonella and Brucella Endocarditis with unique epidemiological and clinical challenges - Qusai Alqudah; Akankcha Alok; Vidya S. Kollu (IDCases)
We present a unique case of simultaneous Bartonella and Brucella endocarditis, the first reported instance of this co-infection, highlighting significant diagnostic and therapeutic challenges. A 63-year-old female with a bioprosthetic mitral valve presented with progressive weakness, weight loss, and a persistent dry cough. Evaluation revealed a large mitral valve vegetation, pulmonary nodules, and mediastinal adenopathy. Despite negative blood cultures and an inconclusive malignancy workup, the high clinical suspicion for culture-negative infective endocarditis prompted further serological testing, which confirmed Brucella IgM, IgG and Bartonella PCR positivity. She underwent successful redo mitral valve replacement, with pathology confirming the diagnosis. This case underscores the importance of detailed exposure history, as a kitten from a flea market emerged as a potential infection source. The coexistence of these pathogens highlights the complexity of culture-negative endocarditis and emphasizes the need for prompt, multidisciplinary management to mitigate poor outcomes.